As with Parents, so with Others and so with God? Relationships among Humanistic Spirituality and Parental and Adult Attachment Styles - Kontrimienė, Simona (Paedagogia Christiana, 2023)
This study (N = 449) explores relationships among humanistic spirituality, which in our Humanistic Spirituality Model encompasses the components of self-actualisation, transcendence and ultimate meaning in life, and parental as well as adult attachment styles as lifelong factors in the origin of spirituality. The results indicate that for female participants, humanistic spirituality is predicted by age and secure adult attachment, whereas for male participants, secure attachment to the mother and secure adult attachment are significant positive predictors. Lastly, the effect of secure attachment to the mother on humanistic spirituality for male participants is direct, while for female participants it is indirect and mediated by secure adult attachment.